Context‐aware user profiles to improve media synchronicity for individuals with severe motor disabilities. (8th March 2021) - Randolph, Adriane B.; Petter, Stacie C.; Storey, Veda C.; Jackson, Melody M.
Abstract: Losing the ability to communicate inhibits social contact, creates feelings of frustration and isolation and complicates personal comfort and medical care. Progressive diseases such as amyotrophic lateral sclerosis (ALS) and multiple sclerosis (MS) can cause severe motor disabilities that make communication through traditional means difficult, slow, and exhausting, even with the support of augmentative and alternative communication (AAC) systems. Using a design science research approach, we seek to improve the communication process for individuals with severe motor disabilities. We develop a series of design requirements to inform the creation and evaluation of an artefact, an AAC system that incorporates context‐aware user profiles to improve the communication process for individuals with severe motor disabilities. We derive prescriptive knowledge through the creation of design principles based on our findings and justify these design principles using the lens of media synchronicity theory (MST). This research identifies opportunities for further research related to MST and provides insights to inform those designing communication systems for individuals that rely on AAC systems.